Hyperglycemic Impact On Sleep Quality In Patients With Type 2 Diabetes Mellitus-A Cross Sectional Study - Elahi, Muhammad Fazl E; Islam, Md Azizul; Khan, Md Reaz Uddin; Ahmed, Rajib; Nosib, Md Nasir Uddin (Bangladesh Armed Forces Medical Journal, 2024)
Background: Diabetes mellitus (DM) causes high morbidity and mortality and loss of quality of life significantly. It is an important public health concern. In epidemiologic studies, people with poor sleep quality are more prone to develop diabetes or metabolism disorder of glucose. Sleep has an important role for metabolic function and specifically homeostasis of glucose metabolism. Many studies have shown a correlation between increased diabetes risk and poor sleep quality or sleep deprivation. DM creates a negative effect impact on quality of sleep on patients. Prevalence of obesity and diabetes becomes greater among aged people, it is of vital importance to fix on sleep for overall medical management. This is aimed to determine hyperglycaemia with sleep quality among the patient. Methods: This was a cross sectional study carried out at Ibrahim General Hospital, National Health Care Network (NHN), Mirpur-10, Dhaka during the period of January 2014 to December 2014. Total 129 respondents were selected purposively for this study. Semi-structured questionnaire was pretested first and then it was used for data collection. Pittsburgh Sleep Quality Index score (PSQI) was used to assess sleep quality. Statistical Package for Social Sciences (SPSS) version 22.0. was used for analysis of the collected data. Results: Among 129 respondents, 98(76%) were male and 31(24%) were female. 93.8% respondents were married and rest 6.2% of them were unmarried. Mean(±SD) age was found 53.64(±9.26) years and range 35 to 70 years. 79.1% of the respondents had co-morbidity of DM, 70(54.3%) had diabetes more than 10 years duration. Mean(±SD) of overall sleep quality score was 9.04(±3.965) and range 1 to 18. Among the respondents of age group >64, 95.70% had poor sleep quality, 76.14% respondents sleep less than 6 hours in a day. So association between sleep quality and glycemic status of type 2 DM was significant(p<0.05). Conclusion: The prevalence of high blood sugar level in Type 2 DM patients have poor sleep quality. Type 2 DM patients with high blood sugar level have to overcompensate kidneys to visit washroom more frequent and lead to disturbance in sleep. Type 2 DM patients with controlled blood sugar level have good sleep quality. It is evident from the study that Type 2 DM patients with high sugar level (Hyperglycaemia) frequently experience sleep difficulties. Bangladesh Armed Forces Med J Vol 56 No (1) June 2023, pp 21-27